(untitled) (PerCursos, 2024)
Due to the high demands in the mental health field, this study aimed to present the use of FG as a tool for the participatory technology development for promoting mental health in Primary Health Care (PHC). This action research was performed in a city in the Midwest of Santa Catarina, Brazil. Data were collected through a focus group that met once. Two professors from the Professional Master’s Program in PHC Nursing and 15 PHC workers from the mental health field participated in the focus group. The information was collected in October 2022, and the data treatment was guided by content analysis. The health workers’ experiences in mental health include a concern with adolescents and women, as they identify the need to implement care practices to strengthen protective and preventive mental health factors. Educational gymkhanas, online psychoeducational interventions, and a podcast emerged as care strategies to be implemented in mental health within PHC. The perceptions of the PHC workers regarding mental health needs and demands enabled defining the public audience and the educational technology that needs to be developed to promote and protect the mental health of PHC service users.